Visual design thinking: a collaborative dimensions framework to profile visualisations. (July 2019) - Bresciani, Sabrina
Abstract : Design Thinking is predominantly visual: a variety of visualisations – from sketches to analytic diagrams – can support designers' work. Each visual format has affordances that constrain and enable specific cognitive and collaborative actions: how can we describe, select and design visualisations for supporting specific phases of the design process? By integrating literature from related domains we developed a "Collaborative Dimensions of Visualisations framework", which allows to distinguish seven traits of visualisations: Structural Restrictiveness, Content Modifiability, Directed Focus, Perceived Finishedness, Outcome Clarity, Visual Appeal and Collaboration Support. Each dimension is described and an illustrative example is provided. The framework is a pragmatic and theoretically grounded discussion tool aimed at helping designers make more informed decisions regarding the visualisations they work with. Highlights: Design Thinking is heavily based on visual practices. Visualisations utilised for Design Thinking have different affordances. A Collaborative Dimensions of Visualisation framework is advanced. The dimensions provide a vocabulary to discuss visualisations' characteristics. The framework is a theoretically grounded evaluation technique.